Pengaruh bentuk takik spesimen baja poros terhadap kekuatan lelah pada pembebanan puntir. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fac. of Geography Gadjah Mada Univ., 2001)
The objective of this study is to observe the effect of notch shapes on fatigue characteristic of shaft steel specimens with torque loading. The specimen is shaft steel with about 0.5 percent of carbon content. The V- notch and U-notch are made to produce stress concentration effect. The value of stress concentration factor was analyzed using a finite element method with Catia Elfini software. Other tests were also conducted including static tension, micro-structure, static torque and hardness the material. The fatigue test with R = 0 result shows that the fatigue strength of V-notch specimen with Kt = 4.48 is lower than the fatigue strength of U-notch specimen with Kt = 2.24. On the 25 kg/mm 2 torque loading, the fatigue strength of U-notch specimen with radius of 1 mm is higher than the fatigue strength of V-notch specimen with notch radius 0.4 mm around 750 %. From the cross section failure area on the same of nominal loading, the pre-crack distribution on front notch surface of V-notch specimens are smoother than U-notch specimens. Generally, fatigue test result on rotary bending and torque loading give the same of crack initiation, crack propagation and static failure mode.